A CASE OF AN INVASIVE CRIBRIFORM BREAST CANCER-ITS SLOW-GROWTH AND DIFFICULTIES OF PRE -OPERATIVE DIAGNOSIS - URASHIMA, Tetsurou; MATSUI, Yoshifumi; OHTA, Takumi; TANIGUCHI, Tetsushi (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2006)
An invasive cribriform breast cancer (ICC) that has a favorable prognosis was first described by Page et al. in 1983. We herein report a case of ICC, including the clinicopathological features. A 48-year-old Japanese woman visited our hospital, complaining of a lump after long-term observation. The tumor was located in the upper area of the right breast. It was 5cm in size, irregular shaped, elastically firm, accompanied by a dimple and fixation to the muscle was recognized. As its malignancy was suggested by ultrasound, computed tomography and magnetic resonance imaging, a core needle biopsy was performed twice. However, we could not reach the final pathological diagnosis. In 2003, radical mastectomy was performed and we finally obtained a pathological diagnosis of ICC (mixed type). The patient is now being followed up at an out-patient clinic without signs of recurrence. It was thought that ICC was slow-growing and ICC might have stratified to an entity that made pre-operative diagnosis by CNB not feasible.